Application of paintable high-conductivity flexible composite material
By optimizing the preparation process and using a muffle furnace to quickly prepare TiN/SrO(SrTiO3)n composite powder, the problems of complex preparation process and low yield of flexible thermoelectric materials are solved, and the flexibility and high conductivity of the materials are achieved. It is suitable for large-scale production and is widely used in thermoelectric and infrared radiation materials.
Patent Information
- Application Number
- CN202510153465.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-12
AI Technical Summary
The existing flexible thermoelectric materials have complex preparation processes and low yields, making them difficult to effectively apply in the flexible field, especially the lack of brittleness and ductility of oxide thermoelectric materials.
Through the optimization of the preparation process, a muffle furnace is used to quickly prepare a coating highly conductive TiN/SrO(SrTiO3)n composite powder, and a flexible composite material with excellent electrical properties is made through a simple coating process.
The flexible and high conductivity of the material is achieved, the preparation process is simplified, suitable for large-scale production, and has shown a wide range of application potential in thermoelectric and infrared radiating materials.
Smart Images

Figure CN119626634A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flexible composite materials, and in particular to the application of a spreadable high-conductivity flexible composite material. Background Art
[0002] At present, flexible thermoelectric materials are widely used in the field of wearable and portable electronic devices due to their excellent plastic deformation ability, lightweight characteristics and concealment. However, in the research of many flexible thermoelectric materials, the traditional preparation process is relatively complicated and has low yield, and it is often difficult to break through the inherent limitations. It is worth mentioning that we innovatively used a muffle furnace to quickly prepare a spreadable strontium titanate block, successfully converting the traditional SrO (SrTiO3) n (n = 1, 2, …, ∞)-based hard ceramic materials are transformed into a paintable conductive material similar to chalk. This unique method makes the material have good writing function and can still maintain high conductivity even when painted on dust-free paper, which is an extremely rare achievement in previous research.
[0003] Conductive polymers have long been considered ideal flexible thermoelectric materials due to their ease of synthesis and good ductility. Compared with traditional inorganic thermoelectric materials, organic materials are more flexible, but their carrier mobility and power output are relatively low. Except for Bi2Te3 alloys, most alloy materials are extremely rare in the application of flexible thermoelectric materials due to their inherent inflexibility, and large-scale energy conversion applications are limited by low reserves and high costs. Although the performance of new thermoelectric materials such as Half-Hassler, clathrates, and cobaltites, as well as traditional oxide thermoelectric materials such as SrTiO3, NaCoO2, and BiCuSeO have been significantly improved, research on these materials in flexible applications is still scarce.
[0004] It is worth noting that compared with intermetallic compounds, oxide materials have the advantages of strong stability, high rare earth abundance, low cost and environmental friendliness. However, due to the natural brittleness and insufficient ductility of inorganic semiconductors and ceramic materials, how to apply oxide thermoelectric materials to flexible fields has always been a technical challenge. Oxide perovskite materials have been widely studied due to their low cost, multiple functionality, environmental friendliness and abundant resources. Our research successfully prepared a soft, spreadable, highly conductive inorganic perovskite thermoelectric material by optimizing the preparation process through a simple and efficient method, providing a new solution for the preparation of flexible thermoelectric materials.
[0005] Compared with traditional materials, this new type of flexible inorganic oxide thermoelectric material not only breaks through the complexity and limitations of material preparation, but also has good thermoelectric properties and infrared radiation performance. In industrial fields such as high-temperature furnaces, it can utilize its high infrared emissivity characteristics and combine it with the Seebeck effect in its thermoelectric properties to recycle the temperature and further improve the utilization rate of energy. Therefore, the flexible materials prepared by it have extremely high application potential and value, and are in urgent need of further development and research to fill the gaps in existing technologies in this field and expand the application scope and efficiency of thermoelectric materials. Summary of the invention
[0006] The purpose of the present invention is to provide an application of a smearable high-conductivity flexible composite material, which is simple to operate, easy to control the operation process, and can quickly and efficiently synthesize TiN / SrO (SrTiO3) n (n=1, 2, …, ∞) composite powder, and a flexible composite material with excellent electrical properties is made through a simple coating process. Among them, TiN / SrO(SrTiO3) n SrTiO3 with (n=1,2, …, ∞) is a basic structural unit, and n represents the number or repetition of the basic unit.
[0007] To achieve the above object, the present invention provides an application of a spreadable high-conductivity flexible composite material, wherein the spreadable high-conductivity flexible composite material TiN / SrO (SrTiO3) n (n=1, 2, …, ∞), including spreadable titanium nitride and strontium titanate composite conductive materials and flexible substrates.
[0008] Preferably, the method comprises the following steps: Preparation of composite conductive material: SrCO3 powder and TiN powder are uniformly mixed and ground, pressed into blocks, wrapped with graphite paper, and sintered to obtain a spreadable high-conductivity titanium nitride and strontium titanate composite block, and the high-conductivity titanium nitride and strontium titanate composite block is ground to obtain a composite conductive powder; the molar ratio of SrCO3 to TiN is X:Y, where X=1 and 0.7 <Y<2; Preparation of high-conductivity flexible composite materials: attaching a composite conductive material to a flexible substrate to form a high-conductivity flexible composite material; the composite conductive material includes a high-conductivity titanium nitride and strontium titanate composite block or a composite conductive powder.
[0009] The following steps are also included: Preparation of composite conductive powder: SrCO3 powder and TiN powder are uniformly mixed and ground, pressed into blocks, wrapped with graphite paper, and fired for the first time to obtain a first composite block of highly conductive titanium nitride and strontium titanate that can be spread, and the first composite block of highly conductive titanium nitride and strontium titanate is ground to obtain the first composite conductive powder TiN / SrO (SrTiO3) n (n = 1, 2,…, ∞); pressing the first composite conductive powder into a block again, placing it in a muffle furnace for a second calcination or vacuum hot pressing sintering to prepare a denser second composite block of titanium nitride and strontium titanate that can be applied, and grinding the second composite block of titanium nitride and strontium titanate to obtain a second composite conductive powder; Preparation of high-conductivity flexible composite material: applying the first composite block or the first composite conductive powder, the second composite block or the second composite conductive powder on a flexible substrate to form a high-conductivity flexible composite material.
[0010] During the first burial, the temperature is 1200-1300℃ and the insulation time is 3-6 hours.
[0011] During the second burial, the temperature is 1400-1600℃ and the insulation time is 5-10 h.
[0012] During vacuum hot pressing sintering, the temperature is 1200-1500°C and the holding time is 1-3 h.
[0013] Preferably, the composite conductive powder is prepared by at least one step of grinding, pressing and sintering.
[0014] Preferably, the flexible substrate comprises an insulating flexible material and a metal foil, wherein the insulating flexible material comprises cellulose, fabric, and paper.
[0015] Preferably, the method comprises the following steps: Preparation of composite conductive material: alkaline earth metal carbonate powder and TiN powder are uniformly mixed and ground, pressed into blocks, wrapped with graphite paper, and sintered to obtain a smearable high-conductivity titanium nitride and alkaline earth metal titanate composite block; the high-conductivity titanium nitride and alkaline earth metal titanate composite block is ground to obtain a composite conductive powder; the molar ratio of alkaline earth metal carbonate to TiN in the composite block is X:Y, wherein X=1 and 0.7 <Y<2; Preparation of high-conductivity flexible composite material: attaching a composite conductive material to a flexible substrate to form a high-conductivity flexible composite material; the composite conductive material includes a composite block or composite conductive powder of high-conductivity titanium nitride and alkaline earth metal titanate. Preferably, the alkaline earth metal carbonate powder includes calcium carbonate powder and barium carbonate powder.
[0016] Preferably, the method of attaching the composite conductive material to the flexible substrate includes: The solution processing method is to disperse the powder in a solvent to form a suspension, and then deposit it on a substrate by coating or dipping, and then form a flexible film after evaporation of the solvent to form a high conductivity flexible composite material; Or use a melt extrusion method, which is to heat and melt before extrusion molding, and then cool to form a high-conductivity flexible composite material; Or using 3D printing technology, a mixture of powder and binder can be printed layer by layer to prepare flexible materials with complex structures and form high-conductivity flexible composite materials; or mixed with a solvent to prepare a paste, which is then applied to a flexible substrate to form a high-conductivity flexible composite material; Or the composite block is applied on a flexible substrate to form a flexible composite material with high electrical conductivity after drying.
[0017] Preferably, the spreadable titanium nitride and strontium titanate composite block is a highly conductive N-type spreadable semiconductor.
[0018] Preferably, the sintering temperature is 1200-1600° C., the holding time is 1-10 h, and the heating rate is 3-10° C. / min.
[0019] Preferably, during pre-pressing, the pressure is 1 MPa-50 MPa.
[0020] Application of spreadable high-conductivity flexible composite materials and high-conductivity titanium nitride and strontium titanate composite powders in thermoelectric materials and infrared radiation materials.
[0021] Therefore, the present invention adopts the application of the above-mentioned spreadable high-conductivity flexible composite material, and its technical effects are as follows: (1) The preparation method is simple and quick, the operation process is easy to control, and it is suitable for large-scale production.
[0022] (2) The composite powder synthesized by solid phase reaction method has good dispersibility and uniformity.
[0023] (3) The composite material has extremely low electrical resistance and is spreadable like chalk, and can be easily coated on various substrates, such as dust-free paper, while still having good conductive properties.
[0024] (4) Composite materials have a high infrared emissivity. Coating in a vacuum high-temperature furnace can reuse the heat and improve energy utilization.
[0025] (5) This material has a wide range of applications and can play an important role in electronic devices, sensors, energy storage and other fields, promoting the development of inorganic oxide flexible conductive ceramics.
[0026] (6) The present invention prepares composite powders by solid-phase reaction method and combines it with coating process to achieve flexibility and high conductivity of the material. This material is not only easy to prepare, but also has a wide range of application potentials and is expected to replace traditional materials in multiple fields such as thermoelectricity and infrared radiation.
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the X-ray diffraction (XRD) pattern of the samples obtained in Examples 1, 2, 3, and 4; Figure 2 This is a schematic diagram of preparing a flexible composite material by coating onto dust-free paper in Example 1; Figure 2 (a) is a resistance test diagram of a flexible material prepared by directly coating the second composite conductive block obtained in Example 1 on dust-free paper; Figure 2 (b) is a test graph of the Seebeck coefficient of a flexible material prepared by directly coating the second composite conductive block obtained in Example 1 on dust-free paper; Figure 2 (c) is a resistance test graph of the second composite conductive powder obtained in Example 1; Figure 2 (d) is a test graph of the Seebeck coefficient of the second composite conductive powder obtained in Example 1; Figure 2 (e) is a resistance test diagram of the second composite conductive block obtained in Example 1; Figure 2 (f) is a test graph of the Seebeck coefficient of the second composite conductive block obtained in Example 1; Figure 3 is the infrared emissivity curve of the sample obtained in Example 1; Figure 4 1 is the X-ray diffraction (XRD) diagram of the samples obtained in Examples 9 and 10. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0031] Example 1 SrCO3 powder and TiN powder were mixed in a molar ratio of 0.7:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0032] The ground mixture was dried at 80 °C for 2 h.
[0033] Use a powder tablet press to press the dried powder at 3MPa for 3 min. After being pressed into blocks, they are wrapped with graphite paper and burned in graphite powder at 1200°C for 3-5 hours using a muffle furnace to obtain a smearable high-conductivity TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) a first composite block, after grinding, a first composite conductive powder of titanium nitride and strontium titanate can be obtained.
[0034] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500 ° C for 6 h to prepare a dense and spreadable TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) a second composite conductive block is ground to obtain a second composite conductive powder.
[0035] As shown in Table 1, the resistance of the first composite conductive block is about 11 Ω, and the Seebeck coefficient is about -8 μV / K; the first composite conductive block is directly applied to dust-free paper to make a flexible material, and the resistance is about 3.5 KΩ; the resistance of the second composite conductive block is about 27 Ω, and the Seebeck coefficient is about -12 μV / K; the resistance of the second composite conductive powder is about 13.5 KΩ, and the Seebeck coefficient is -11 μV / K; the second composite conductive block is directly applied to dust-free paper to make a flexible material, and the resistance is about 26 KΩ, and the Seebeck coefficient is -33 μV / K. In particular, the resistance of the flexible material coated on the dust-free paper is related to the amount of coating. When 0.005 g of the first composite conductive powder material is coated per square centimeter, the resistance is about 3520.6 Ω; when 0.01 g of the first composite conductive powder material is coated per square centimeter, the resistance is about 3359.4 Ω; when 0.02 g of the first composite conductive powder material is coated per square centimeter, the resistance is about 3196.0 Ω.
[0036] Since the conductivity of strontium titanate is highly dependent on the concentration of oxygen vacancies, high temperatures accelerate the diffusion of oxygen atoms into the lattice due to the incomplete isolation of oxygen, filling the oxygen vacancies and reducing the carrier concentration. At the same time, high temperatures promote the complete oxidation of TiN, making Ti 3+ To Ti 4+ The transformation reduces the free electron concentration and further reduces the carrier concentration, which increases the resistance of the second composite conductive bulk.
[0037] Table 1 Test results of resistance and Seebeck coefficient of the product in Example 1 ; like Figure 2As shown, the TiN / SrO(SrTiO3)n (n = 1, 2, …, ∞) second composite conductive block obtained in Example 1 is directly coated on dust-free paper, and the resistance and Seebeck coefficient test graphs of the second composite conductive powder and the second composite conductive block sample indicate the application of the spreadable high-conductivity flexible composite material and the high-conductivity titanium nitride and strontium titanate composite powder prepared in the present application in flexible thermoelectric materials.
[0038] like Figure 3 As shown, the infrared emissivity curve of the sample obtained in Example 1. The average infrared emissivity of the sample at the 8-14 μm atmospheric window is higher than 0.95; the average infrared emissivity at the 3-5 μm atmospheric window is higher than 0.94. This shows the application prospects of the spreadable high-conductivity flexible composite material and the high-conductivity titanium nitride and strontium titanate composite powder prepared in this application in high infrared radiation materials.
[0039] Example 2 SrCO3 powder and TiN powder were mixed in a molar ratio of 0.8:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0040] The ground mixture was dried at 80 °C for 2 h.
[0041] The dried powder was pressed at 3MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder was then burned in a muffle furnace at 1200°C for 3-5h in graphite powder to obtain a smearable high-conductivity TiN / SrO (SrTiO3). n (n= 1, 2, …, ∞) The first composite block has a resistance of about 12.9 Ω, and after grinding, a first composite conductive powder of titanium nitride and strontium titanate can be obtained.
[0042] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500 ° C for 6 h to prepare a dense and spreadable TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) The second composite conductive block has a resistance of about 26.6 Ω.
[0043] Example 3 SrCO3 powder and TiN powder were mixed in a molar ratio of 0.9:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0044] The ground mixture was dried at 80 °C for 2 h.
[0045] The dried powder was pressed at 3MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder was then burned in a muffle furnace at 1200°C for 3-5h in graphite powder to obtain a smearable high-conductivity TiN / SrO (SrTiO3). n (n= 1, 2, …, ∞) The first composite block has a resistance of about 20.4 Ω, and after grinding, the first composite conductive powder of titanium nitride and strontium titanate can be obtained.
[0046] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500 ° C for 6 h to prepare a dense and spreadable TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) The second composite conductive block has a resistance of about 45.3 Ω.
[0047] Example 4 SrCO3 powder and TiN powder were mixed in a molar ratio of 1:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0048] The ground mixture was dried at 80 °C for 2 h.
[0049] The dried powder was pressed at 3MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder was then burned in a muffle furnace at 1200°C for 3-5h in graphite powder to obtain a smearable high-conductivity TiN / SrO (SrTiO3). n (n= 1, 2, …, ∞) The first composite block has a resistance of about 25.8Ω, and after grinding, a first composite conductive powder of titanium nitride and strontium titanate can be obtained.
[0050] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500 ° C for 6 h to prepare a dense and spreadable TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) The second composite conductive block has a resistance of about 50.1 Ω.
[0051] like Figure 1 As shown, it is shown that, for the raw materials SrCO3 powder and TiN powder, the lower the SrCO3 content, the easier it is to synthesize TiN / SrTiO3, that is, n=∞, TiN / SrO(SrTiO3)n (n=1, 2, …, ∞).
[0052] Example 5 SrCO3 powder and TiN powder were mixed in a molar ratio of 1:0.8, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0053] The ground mixture was dried at 80 °C for 2 h.
[0054] The dried powder was pressed at 3 MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder was then burned in a muffle furnace at 1200 °C for 3-5 h in graphite powder to obtain a smearable high-conductivity TiN / SrO (SrTiO3). n (n= 1, 2, …, ∞) The first composite block can be ground to obtain a first composite conductive powder of titanium nitride and strontium titanate.
[0055] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500 °C for 6 h to prepare a dense and spreadable TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) a second composite conductive block.
[0056] Example 6 SrCO3 powder and TiN powder were mixed in a molar ratio of 0.8:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0057] The ground mixture was dried at 80 °C for 2 h.
[0058] The dried powder was pressed at 3 MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder was then burned in a muffle furnace at 1200 °C for 3-5 h in graphite powder to obtain a smearable high-conductivity TiN / SrO (SrTiO3). n (n= 1, 2, …, ∞) The first composite block can be ground to obtain a first composite conductive powder of titanium nitride and strontium titanate.
[0059] The first composite conductive powder is hot pressed and sintered at 1200℃ and 10MPa for 2 h to prepare a dense and spreadable TiN / SrO (SrTiO3) n (n = 1, 2, …, ∞) The second composite conductive block has a resistance of about 110 Ω, and when it is smeared on dust-free paper, it is about 112.6 MΩ.
[0060] The pressing is only for shaping the sample, and the pressing strength has a certain influence on its density. The greater the pressing strength, the greater its density. It has little influence on the resistance of the first composite block and the first composite conductive powder.
[0061] In this embodiment, a two-time molding and sintering method is adopted, and the density of the powder or block obtained by sintering once is increased, thereby increasing the adhesion of the powder on the flexible substrate and increasing the stability of the high-conductivity flexible composite material.
[0062] Example 7 The TiN / SrO (SrTiO3) obtained in Example 1 n (n = 1, 2, …, ∞) The first composite powder is mixed with alcohol and stirred evenly to obtain a paste.
[0063] The paste was spread on a dust-free paper and dried at 60°C for 5 min.
[0064] The resistance of the prepared flexible composite material was tested, and the results showed that its resistance was low, and the specific value was related to the amount of the coating. When 0.005 g of the first composite powder was coated per square centimeter, the resistance was about 3520.6 Ω; when 0.01 g of the first composite powder was coated per square centimeter, the resistance was about 3359.4 Ω; when 0.02 g of the first composite powder was coated per square centimeter, the resistance was about 3196.0 Ω.
[0065] Example 8 The TiN / SrO (SrTiO3) obtained in Example 1 n (n = 1, 2, …, ∞) The second composite conductive powder is mixed with alcohol and stirred evenly to obtain a paste.
[0066] The paste was spread on a dust-free paper and dried at 60°C for 5 min.
[0067] The resistance of the prepared flexible composite material was tested, and the results showed that its resistance was low, and the specific value was related to the amount of the coating. When 0.005 g of the second composite conductive powder was coated per square centimeter, the resistance was about 20192.7 Ω; when 0.01 g of the second composite conductive powder was coated per square centimeter, the resistance was about 23761.2 Ω; when 0.02 g of the second composite conductive powder was coated per square centimeter, the resistance was about 26568.3 Ω.
[0068] Example 9 CaCO3 powder and TiN powder were mixed in a molar ratio of 1:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0069] The ground mixture was dried at 80 °C for 2 h.
[0070] The dried powder is pressed at 3 MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder is then burned in a muffle furnace at 1200°C for 3-5 h in graphite powder to obtain a spreadable high-conductivity TiN / CaTiO3 first composite block. After grinding, a first composite conductive powder of titanium nitride and calcium titanate is obtained.
[0071] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500°C for 6 h, so that a denser, spreadable TiN / CaTiO3 second composite conductive block with a resistance of about 41.2 Ω could be prepared.
[0072] Example 10 BaCO3 powder and TiN powder were mixed in a molar ratio of 1:1, and an appropriate amount of anhydrous ethanol was added as a solvent for grinding for 3 h.
[0073] The ground mixture was dried at 80 °C for 2 h.
[0074] The dried powder is pressed at 3 MPa for 3 min using a powder tablet press, and then wrapped with graphite paper. The powder is then burned in a muffle furnace at 1200°C for 3-5 h in graphite powder to obtain a spreadable high-conductivity TiN / BaTiO3 first composite block. After grinding, a first composite conductive powder of titanium nitride and barium titanate is obtained.
[0075] The first composite conductive powder was pressed into a block again at 1 MPa for 3 min, and placed in a muffle furnace for graphite calcination at 1500°C for 6 h, so that a denser, spreadable TiN / BaTiO3 second composite conductive block with a resistance of about 43.6 Ω could be prepared.
[0076] like Figure 4 As shown, barium carbonate and calcium carbonate can replace strontium carbonate to prepare spreadable, highly conductive, flexible composite materials.
[0077] Therefore, the present invention adopts the application of the above-mentioned spreadable high-conductivity flexible composite material, which is simple to operate and easy to control the operation process, and can quickly and efficiently synthesize TiN / SrO (SrTiO3) n , (n = 1, 2, …, ∞) composite powders, and flexible composite materials with excellent electrical properties are made through a simple coating process.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An application of a spreadable high-conductivity flexible composite material, characterized in that: The smearable high-conductivity flexible composite material TiN / SrO (SrTiO3) n , n = 1, 2, …, ∞, including spreadable titanium nitride and strontium titanate composite conductive materials and flexible substrates.
2. The use of a spreadable high-conductivity flexible composite material according to claim 1, characterized in that: The following steps are involved: Preparation of composite conductive material: SrCO3 powder and TiN powder are uniformly mixed and ground, pressed into blocks, wrapped with graphite paper, and sintered to obtain a spreadable high-conductivity titanium nitride and strontium titanate composite block, and the high-conductivity titanium nitride and strontium titanate composite block is ground to obtain a composite conductive powder; the molar ratio of SrCO3 to TiN is X:Y, where X=1 and 0.7 <Y<2; Preparation of high-conductivity flexible composite materials: attaching a composite conductive material to a flexible substrate to form a high-conductivity flexible composite material; the composite conductive material includes a high-conductivity titanium nitride and strontium titanate composite block or a composite conductive powder.
3. The use of a spreadable high-conductivity flexible composite material according to claim 2, characterized in that: The composite conductive powder is prepared by at least one step of grinding, pressing and sintering.
4. The use of a spreadable high-conductivity flexible composite material according to claim 1, characterized in that: The flexible substrate includes insulating flexible materials and metal foils, wherein the insulating flexible materials include cellulose, fabric, and paper.
5. The use of a spreadable high-conductivity flexible composite material according to claim 2, characterized in that: The strontium carbonate may also be replaced by one or more of calcium carbonate and barium carbonate.
6. The use of a spreadable high-conductivity flexible composite material according to claim 2, characterized in that: Methods of attaching the composite conductive material to the flexible substrate include The solution processing method is to disperse the powder in a solvent to form a suspension, and then deposit it on a substrate by coating or dipping, and then form a flexible film after evaporation of the solvent to form a high conductivity flexible composite material; Or use a melt extrusion method, which is to heat and melt before extrusion molding, and then cool to form a high-conductivity flexible composite material; Or using 3D printing technology, a mixture of powder and binder can be printed layer by layer to prepare flexible materials with complex structures and form high-conductivity flexible composite materials; or mixed with a solvent to prepare a paste, which is then applied to a flexible substrate to form a high-conductivity flexible composite material; Or the composite block is applied on a flexible substrate to form a flexible composite material with high electrical conductivity after drying.
7. The use of a spreadable high-conductivity flexible composite material according to claim 2, characterized in that: The spreadable titanium nitride and strontium titanate composite bulk is a highly conductive N-type spreadable semiconductor.
8. The use of a spreadable high-conductivity flexible composite material according to claim 2, characterized in that: The sintering temperature is 1200-1600°C, the holding time is 1-10h, and the heating rate is 3-10°C / min.
9. The use of a spreadable high-conductivity flexible composite material according to claim 2, characterized in that: During pre-pressing, the pressure is 1MPa-50MPa.
10. Use of the spreadable high-conductivity flexible composite material and the high-conductivity titanium nitride and strontium titanate composite powder according to any one of claims 1 to 9 in thermoelectric materials and infrared radiation materials.
Citation Information
Patent Citations
Preparation method of flexible pyroelectric film
CN104209524A
Boron carbide-titanium boride lightweight high-strength composite ceramic material and preparation method thereof
CN113387704A
Strontium titanate / boron nitride nanotube composite ceramic core block and preparation method and application thereof
CN119118658A
Reduced oxides having large thermoelectric ZT values
US20130240801A1